ANALISIS FRAMING PEMBERITAAN KEBAKARAN HUTAN DAN LAHAN PT. AGRO SINERGI NUSANTARA PADA MEDIA ONLINE LOKAL DAN NASIONAL - Mullah Oges Cabucci; Putri Maulina (Universitas Tidar, 2021)
This study discusses the impact of news coverage on PT. Agro Sinergi Nusantara due to forest and land fires in the area of Business Use Rights (HGU) in the company covering an area of seven hectares, and this study uses the Framing Analysis method. The researcher chose two news stories from online news media: acehportal.com as local sources; and antarnews.com as a national source for analysis. This study uses the Qualitative Method of Framing Analysis by Mr. Pan, Zhongdang and Mr. M.Kosicki, Gerald. This finding showing that the two media focused heavily on the company and were not objective about the fire incident at PT.Agro Sinergi Nusantara without looking at the facts and realities, and did not involve sources from the company that actually occurred in the field. So that it forms a social construction that leads readers to consider the company PT.Agro Synergy Nusantara as the main object.